Basic Assumptions of Organizational Behavior - Basnet, Bhupindra Jung (NCC Journal, 2019)
The purpose of this paper is to do in depth analysis of the basic assumptions of organizational behavior. This paper is based on conceptual base reviewed from different books and research reports. The objective of the study is to identify the basic assumptions of organizational behavior. The paper concludes that there are two types of basic assumptions of organizational behavior. They are nature of people and nature of organizations. A basic assumption about nature of people incorporates individual differences, a whole person, and motivated behavior, value of the person, selective perception, and desire for involvement. A basic assumption about nature of organizations involves social system, mutuality of interest, and ethical treatment.